Electrochemical dissolution and retrieval of broken NiTi endodontic files from root canal using chloride based isotonic fluids as electrolytes − An in vitro study - Joy Basil; Kuriakose Feby; Sudhakar Aswathy S; Soumya T. S; Pathrose Sonia P (Wolters Kluwer Medknow Publications, 2024)
ObjectiveThe electrochemical dissolution method of instrument retrieval emphasizes on the dissolution of the instrument rather than sacrificing dentine. Most of the studies conducted for electrochemical dissolution used fluoride-containing electrolytes and were performed inside a beaker. In this study, we used chloride-based fluids as electrolytes. Materials and MethodsFifty extracted mandibular first premolars were divided into five groups based on the electrolytes used. Canals were enlarged to ProTaper Universal F2, and files were intentionally broken inside the canal. These specimens were subjected to electrochemical characterization by applying the potential of 9V for 20 min. Optical images were taken to assess the change in surface topography. The results were analyzed statistically by one-way analysis of variance (analysis of variance [ANOVA]). ResultsThe rate of dissolution based on the electrolyte used decreased in the following order, viz. Tyrode's solution>artificial saliva>normal saline>Ringer's lactate/physiological serum. ConclusionApart from fluoride, chloride-based electrolytes could be an efficient alternative.